The Effectiveness of English Day Program to Improve the Students Speaking Ability at Senior High School Zainul Hasan 1 Genggong - Jumroatul Lailia Ningsih; Mamlu’atun Ni’mah; Beny Hamdani (Jurnal Kewarganegaraan, 2022)
AbstractEnglish day is a daily program where this activity is carried out every day for a month in order to determine the effectiveness or development of speaking in the rest of class XI at Senior High School Zainul Hasan 1 Genggong High. The purpose of this study is 1)To determine the fluency of students' speaking in the eleventh grade before the English Day program. 2)To familiarize students with speaking English every day in class. 3)To improve the speaking of students in the eleventh grade by using tool speaking fluency, memorize vocabulary, spel pronounciation, story telling. The research method used by the researcher is a qualitative method. Data collection techniques used in the study were in-depth interviews, observation, and documentation. The data validity technique uses the alternative hypothesis and the zero hypothesis. The data analysis technique uses questionnaires and tests. The results of this study indicate that the English Day program is very influential in improving students' speaking.Keyword: Effectiveness, English day program, Students Speaking Ability AbstrakEnglish day merupakan program harian dimana kegiatan ini dilakukan setiap hari selama satu bulan dalam rangka mengetahui efektifitas atau perkembangan speaking pada siswa kelas XI selebihnya di SMA Zainul Hasan 1 Genggong. Tujuan dari penelitian ini adalah 1)Untuk mengetahui kelancaran berbicara siswa di kelas sebelas sebelum program English Day. 2) Membiasakan siswa berbicara bahasa Inggris setiap hari di kelas. 3) Untuk meningkatkan kemampuan berbicara siswa di kelas sebelas dengan menggunakan alat kelancaran berbicara, menghafal kosa kata, pengucapan ejaan, bercerita. Metode penelitian yang digunakan oleh peneliti adalah metode kualitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah wawancara mendalam, observasi, dan dokumentasi. Teknik validitas data menggunakan hipotesis alternatif dan hipotesis nol. Teknik analisis data menggunakan angket dan tes. Hasil penelitian ini menunjukkan bahwa program English Day sangat berpengaruh dalam meningkatkan kemampuan berbicara siswa.Kata Kunci: Keefektifan, English day program, Meningkatkan berbicara siswa